To adjust or not to adjust: Cut-off scores in performance validity testing in Portuguese older adults with dementia - Fernandes, Sandra; Ferreira, Inês; Querido, Luís; Daugherty, Julia C. (Frontiers in Psychology, 2022)
The rising demographic of older adults worldwide has led to an increase in dementia cases. In order to ensure the proper allocation of care and resources to this clinical group, it is necessary to correctly distinguish between simulated versus bona-fide cognitive deficits typical of dementia. Performance Validity Tests (PVTs) are specifically designed to assess a lack of effort and the possible simulation of cognitive impairment. Previous research demonstrates that PVTs may be sensitive to dementia, thus inaccurately classifying real memory impairment as simulation. Here, we analyzed the sensitivity of PVTs in discriminating between dementia and simulation using receiver operating characteristic (ROC) curve analyses. Further, we examined the potential need for adjusting cut-off scores for three stand-alone (Test of Memory Malingering, Rey-15 Item Memory Test, and Coin in Hand-Extended Version) and one embedded (Reliable Digit Span) PVT for Portuguese older adults with dementia. The results showed that (1) all measures, except for the Coin in Hand— Extended version (CIH-EV), were sensitive to one or more sociodemographic and/or cognitive variables, and (2) it was necessary to adjust cut-off points for all measures. Additionally, the Rey-15 Item Memory Test did not demonstrate sufficient discriminating capacity for dementia. These results present important implications for clinical practice and the daily life of patients, as the use of incorrect cut-off points could impede patients from getting the resources they need.